Haemosporidian blood parasite diversity and prevalence in the semi-collared flycatcher (Ficedula semitorquata) from the eastern Balkans - Peev, Strahil; Zehtindjiev, Pavel; Ilieva, Mihaela; Träff, Johan; Briedis, Martins; Adamík, Peter (Parasitology international, 2016)
We present the first survey on prevalence and diversity of haemosporidian parasites of the genera Plasmodium and Haemoproteus in a poorly studied migratory passerine, the semi-collared flycatcher (Ficedula semitorquata). In total, 110 individuals were sampled during two breeding seasons in Eastern Bulgaria. We collected both blood samples for PCR identification and blood films for microscopic identification of haemosporidians. We found six distinctive parasite cyt b lineages present in the blood of the semi-collared flycatcher (three Haemoproteus and three Plasmodium). Two of the lineages, i.e. pWW3 of Plasmodium sp. and hCCF2 of Haemoproteus sp., are recorded for the first time in the family Muscicapidae. The overall prevalence ranged between 12.2 and 15.9% and we did not find co-infections. We hypothesize that the low prevalence of haemosporidians in this species might be linked to its small population size and relatively restricted geographical range.
Keywords: Cytochromes b; Protozoan Infections; Haemosporida; Haemoproteus; nemoci ptáků; zvířata; Semi-collared flycatcher; Bird Diseases; Avian malaria; cytochromy b; Plasmodium; protozoální infekce; zpěvní ptáci; Balkan Peninsula; PCR; Balkánský poloostrov; Songbirds; Animals